An open-source technology platform to increase reproducibility and enable high-throughput production of tailorable gelatin methacryloyl (GelMA) - based hydrogels - Eggert, Sebastian; Kahl, Melanie; Bock, Nathalie; Meinert, Christoph; Friedrich, Oliver; Hutmacher, Dietmar W. (Materials and Design, 2021)
Gelatin methacryloyl (GelMA)-based hydrogels have become highly studied as modular tissue culture platforms due to the combination of the bioactivity of gelatin and tailorability of photo-crosslinkable hydrogels. However, current production and characterization workflows still rely on manual, time-consuming, and low-throughput processes, ultimately limiting widespread adaption. To address these challenges, an open-source technology platform is engineered and validated for automated high-throughput production of GelMA-based 3D constructs by integrating automated pipetting capabilities for viscous and non-viscous liquids. Firstly, the platform is applied in combination with inexpensive absorbance measurements to systematically optimize the mixing sequence for GelMA-based precursor solutions. This enables a decrease in the relative standard deviation of the prepared mixtures from 63% to 2.5%, demonstrating a significantly improved reproducibility. Next, the applicability and high-throughput capacity are demonstrated by the reproducible generation of GelMA dilution series with 0.5 and 2% (w/v) concentration steps as well as double network hydrogels consisting of 2% (w/v) alginate and 5% (w/v) GelMA. Finally, a simple and user-friendly methodology is described that integrates Design of Experiments approaches to systematically study the combinatorial effects of material and crosslinking parameters and to establish a parameter library for on-demand production of mechanically defined GelMA-based hydrogels. The platform enables reproducible production and offers an open-source and accessible alternative to high-priced liquid-handling robots and bioprinters.
CRIS-Team Scopus Importer:2021-04-02
Keywords: 3D cell culture; Bioprinting; Gelatin methacryloyl (GelMA); Hydrogels; Open-source; Reproducibility; Tissue engineering